Efektivitas Teknik Time-Out untuk Mengurangi Perilaku Bullying pada Anak Dengan Gangguan Emosi dan Perilaku - Intan Meliafi Risa; Marlina; Mega Iswari; Johandri Taufan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by the high level of bullying behavior carried out by children with emotional and behavioral disorders in the school environment. This study aims to analyze the effectiveness of the time-out technique in reducing bullying behavior in children with emotional and behavioral disorders at SDN 12 Pisang. The research method used a quantitative approach with a Single Subject Research (SSR) design with an A–B–A pattern consisting of an initial baseline phase (A1), an intervention phase (B), and a second baseline phase (A2). The subject of the study was a fifth-grade student identified as having emotional and behavioral disorders with a high level of verbal bullying. Data were collected through direct observation using behavior frequency recording, supported by interviews and documentation. Data analysis was carried out using visual analysis within and between conditions, including directional trends, data stability, level changes, and overlap percentages. The results showed that the frequency of bullying behavior in the initial baseline phase was at a stable number of 6 times per session. After being given intervention using the time-out technique, the frequency of behavior decreased to 4–5 times, and in the second baseline phase it decreased further to 2–3 times per session. These results indicate that the time-out technique is effective in reducing bullying behavior in children with emotional and behavioral disorders.